2020
DOI: 10.1016/j.annepidem.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Postrelease mortality among persons hospitalized during their incarceration

Abstract: Health and mortality of people released from incarceration have received increased attention, and yet little is known about the postrelease experiences of those hospitalized during incarceration. Methods: For persons incarcerated and released from the North Carolina (NC) state prison system between January 1, 2008, and June 30, 2015, we examined postrelease mortality from 2008 to 2016 by history of prison hospitalization. Results: Among 111,479 released persons, 0.9% (n ¼ 1010) were hospitalized during their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Of the 26 studies reporting on suicide, most ( n = 23) reported using the International Classification of Diseases (ICD) to define death by suicide. Of the 26 suicide studies, 11 examined confirmed deaths by suicide exclusively (e.g., ICD9: E950, E959, ICD10: X60, X84) [ 14 , 39 47 , 61 ], three included both suicide and unnatural deaths with undetermined intent (e.g., ICD10: X60, X84, Y10, Y34) [ 48 50 ], and 12 did not provide detailed information about suicide definitions [ 51 60 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 26 studies reporting on suicide, most ( n = 23) reported using the International Classification of Diseases (ICD) to define death by suicide. Of the 26 suicide studies, 11 examined confirmed deaths by suicide exclusively (e.g., ICD9: E950, E959, ICD10: X60, X84) [ 14 , 39 47 , 61 ], three included both suicide and unnatural deaths with undetermined intent (e.g., ICD10: X60, X84, Y10, Y34) [ 48 50 ], and 12 did not provide detailed information about suicide definitions [ 51 60 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies are outlined in Table 1 . The 11 included studies [ [10] , [11] , [12] , [13] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ] contained 988,553 people released from incarceration and 4,835 violence-related deaths (range 68-1,708 violence-related deaths). The studies were published between 2007 and 2020 and had a median follow-up period of 13 years (interquartile range 8-16 years).…”
Section: Resultsmentioning
confidence: 99%